Manufacture of dahi from skim milk adding mango juice - Kabir, MA; Rashid, MH; Hassan, MN; Afroz, MF; Miraz, FH (Bangladesh Journal of Animal Science, 2014)
The aim of this research was to prepare and evaluate the quality of dahi using skim milk fortified with 5, 10 and 15 percent of mango juice. The quality of prepared dahi was measured by organolaptic, chemical and microbiological tests. Significant difference was observed within the smell and taste score (p<0.05), the body and consistency score (p<0.01) and color and texture (p<0.05) of different types of dahi. Fat, ash and total solids content differed significantly (p<0.05) among the different types of dahi with mango juice but protein content and pH values did not differ significantly (p>0.05) among the different types of dahi with mango juice. There was no significant difference (p>0.05) in case of total viable organisms count but significant difference (p<0.05) was found in case of Coliform count among the different types of dahi with mango juice. From this study it was suggested that dahi could be prepared successfully by adding different proportion of mango juice with skim milk and 10% mango juice addition showed better result. DOI: http://dx.doi.org/10.3329/bjas.v43i2.20713 Bang. J. Anim. Sci. 2014. 43 (2): 128-131